An investigation into recruitment, retention and motivation of advanced life support practitioners in South Africa - Gangaram, Padarath (Division of Emergency Medicine, 2017)
Background: Internationally, emergency medical services (EMS) are experiencing problems with recruiting, retaining and motivating advanced life support (ALS) practitioners. The persistent shortage of ALS practitioners in South Africa (SA) poses a challenge to the effective delivery of prehospital emergency medical care. The global demand for SA trained ALS practitioners is steadily increasing. SA EMS organisations are struggling to compete for these practitioners with the international market. The SA EMS industry currently has no effective approach to decrease the loss of ALS practitioners. This research study was therefore conceptualized to investigate factors that influence ALS practitioner recruitment, retention and motivation in an effort to enhance them. Methods: This study followed a sequential, explanatory, mixed method design. The two phase study was non-experimental and descriptive in nature. The quantitative phase was comprised of ALS practitioners (n=1309) and EMS managers (n=60) completing questionnaires. The qualitative phase of the study involved data gathering through focus group (n=7) discussions with ALS practitioners and semi-structured interviews with EMS managers (n=6). Quantitative data was analysed with Statistical Package for the Social Sciences (SPSS). Inferential techniques included the use of correlations and chi squared test values which were interpreted using p-values. Results: The study identified 19 recruitment, 25 retention and 16 motivation factors that influence ALS practitioners. Cumulatively, these factors revolved around the ALS practitioners' work environment, professional development and employment package. Strong recruitment factors that were identified include: ALS practitioner remuneration, skilled EMS management and organisation culture. Similarly, strong ALS practitioner retention factors that were identified include: skilled EMS management, remuneration, resources, availability of health and wellness programmes, recognition of practitioners, working conditions and safety and security. Strong ALS practitioner motivation factors included: remuneration, skilled EMS management and resources. Conclusion: More ALS practitioner training institutions are required to improve the number of these practitioners. EMS organisations must improve the work environment, employment package and professional development opportunities for ALS practitioners. Such practices will encourage ALS practitioner recruitment, retention and motivation.